Laparoscopic intraperitoneal mesh repair of an incisional hernia after transverse rectus abdominis myocutaneous flap reconstruction for breast cancer. Issue 3 (6th March 2022) - Nitta, Toshikatsu; Suga, Keiji; Ohta, Masato; Kataoka, Jun; Ishii, Masatsugu; Ueda, Masahiko; Senpuku, Sadakatsu; Iida, Ryo; Ishibashi, Takashi
Abstract: Breast reconstruction with transverse rectus abdominis myocutaneous (TRAM) flap is performed for the treatment of large defects of the breast. However, this may result in an abdominal wall hernia or bulging. A 53‐year‐old Japanese woman with left breast cancer underwent left skin‐sparing mastectomy, sentinel node lymph node dissection, and immediate reconstruction with a contralateral pedicled TRAM flap. Thirty‐two months following surgery, right lower abdominal wall hernia (15.5 × 12 cm) and bulging were observed at the suprapubic region. The patient was diagnosed with an incisional hernia and was scheduled for laparoscopic intraperitoneal mesh repair. The mesh was coated with an absorbable hydrogel barrier and was trimmed to 26 × 22 cm, with a 5 cm overlap around the defect. The patient demonstrated a good postoperative course. In conclusion, intraperitoneal onlay mesh with hernia repair closure (IPOM‐Plus) is a simple and useful method for hernia repair following TRAM flap reconstruction.